Mitigating Turbidity in the Mandroseza Basin: Potential of High-Flow Pump Integration with Flocculant-Assisted Decantation Pretreatment - Andrianarivony Tiona; Robijaona Rahelivololoniaina Baholy (Britain International of Exact Sciences (BIoEx) Journal, 2025)
The increasing challenge of sediment-laden inflows to the Mandroseza Basin, the primary raw water source for Antananarivo, Madagascar, necessitates effective pretreatment strategies to safeguard water treatment plant efficiency. This study investigates the integration of a high-flow pumping system with flocculant-assisted decantation to mitigate seasonal turbidity spikes. Laboratory-scale static and dynamic sedimentation tests were conducted to evaluate the performance of aluminium sulfate, sodium silicate, cationic polyacrylamide (PAM), and polyethylene oxide (PEO). Results from jar tests indicated optimal dosage ranges for each flocculant, guiding subsequent dynamic settling experiments under simulated operational conditions. PAM, at 5-6 mg/kg, and PEO, at 17-18 mg/kg, consistently outperformed sodium silicate, demonstrating superior supernatant clarity (TSS of 46 mg/L and 35 mg/L, respectively) and enhanced sludge compaction. Flattening tests further confirmed the cohesive and dense nature of PAM and PEO-induced sludge. While sodium silicate offered moderate performance, its lower efficiency in fine particulate removal makes it less suitable for stringent clarity requirements. The findings suggest that integrating optimized PAM or PEO dosing with high-flow conveyance presents a promising, scalable solution for managing turbidity at the intake, reducing the load on downstream treatment processes and improving overall plant sustainability. Future research should focus on field validation and comprehensive cost-benefit analysis for large-scale implementation in urban water supply systems facing similar seasonal sedimentation challenges.